Differences in factors influencing orthodontists’ consideration of clear aligners, satisfaction, and stability levels in a capital city: a cross-sectional study - Husna, Asmaul; Purbiati, Maria; Purwanegara, Miesje Karmiati; Develas, Deo (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2025)
ABSTRACTIntroduction: With the increasing number of adult orthodontic patients, there is also a growing demand for more aesthetic and comfortable treatments. Clear aligners are a quite new treatment technique in the field of orthodontics that is being developed using digital-based technology, and their usage is increasing due to their perceived aesthetic and comfortable nature. This research objective was to analyze differences in factors influencing orthodontists’ consideration of clear aligners, satisfaction, and stability levels in a capital city. Methods: This comparative analytical study with a cross-sectional design was conducted to examine the perception of orthodontists in a capital city in Indonesia, Jakarta, regarding the use of clear aligners. Fifty orthodontists taken through Slovin sampling technique, were given a set of questionnaires and divided into two groups based on users and non-users of aligner. The survey utilized a questionnaire consisting of 17 questions with both clinical and satisfactionary criteria, which were sent online via WhatsApp Messenger to the respondents. To compare the data were analyzed by the chi square test statistically. Results: Most of respondent practiced in elite areas of South Jakarta, 52.2%, among other 4 differences cities were observed in the perception of orthodontists who were 46% users and 54% non-users aligner regarding periodontal health factors, treatment efficiency, pain complaints, root resorption, satisfaction levels, and treatment outcome stability. Both clear aligners users and non-users have similar perceptions regarding treatment cost factors influencing the usage of clear aligners, improved oral hygiene, minimal white spot lesions, and better aesthetics. Conclusion: Some parameters were not different, especially for the parameters of treatment cost as a negative perception, and oral hygiene, white spot lesion, and aesthetics, all of which gave similar positive perceptions rated by respondents. This is good considerably for an aligner producer. Keywords clear aligner users and non-users, capital city, orthodontists perception Perbedaan faktor-faktor yang mempengaruhi pertimbangan penggunaan clear aligners, tingkat kepuasan, dan stabilitas oleh ortodontis di sebuah ibu kota negara: studi potong lintang ABSTRAK Pendahuluan: Dengan meningkatnya jumlah pasien ortodontik dewasa, permintaan akan perawatan yang lebih estetis dan nyaman juga meningkat. Clear aligner merupakan teknik perawatan yang cukup baru di bidang ortodontik yang sedang dikembangkan menggunakan teknologi berbasis digital, dan penggunaannya semakin meningkat karena sifatnya yang estetis dan nyaman. Tujuan penelitian ini adalah untuk menganalisis Perbedaan faktor-faktor yang mempengaruhi pertimbangan penggunaan clear aligners, tingkat kepuasan, dan stabilitas oleh ortodontis di sebuah ibu kota negara. Metode: Metode penelitian analitik komparatif dengan desain potong lintang  dilakukan melalui teknik sampling Slovin, untuk mengkaji persepsi ortodontis di Jakarta, sebuah ibukota negara, Indonesia, mengenai penggunaan clear aligner. Sebanyak lima puluh ortodontis di Jakarta, diberikan kuesioner dan dibagi menjadi dua kelompok berdasarkan pengguna dan bukan pengguna aligner. Survei menggunakan kuesioner dengan 17 pertanyaan tentang reaksi klinis dan kepuasan, yang dikirimkan secara online melalui WhatsApp Messenger kepada responden. Data dianalisis secara statistik dengan uji Chi-Square. Hasil: Sebagian besar responden berpraktik di kawasan elit Jakarta Selatan, 52,2%, di antara 4 kota lainnya perbedaan diamati pada persepsi ortodontis yang merupakan 46% pengguna dan 54% bukan pengguna aligner mengenai faktor kesehatan periodontal, efisiensi perawatan, keluhan nyeri, resorpsi akar, tingkat kepuasan, dan stabilitas hasil perawatan. Baik pengguna clear aligner maupun bukan pengguna memiliki persepsi yang sama mengenai faktor biaya perawatan yang memengaruhi penggunaan clear aligner, peningkatan kebersihan mulut, minimalnya white spot lesion, dan estetika yang lebih baik. Simpulan: Beberapa parameter tidak berbeda, terutama untuk parameter biaya perawatan sebagai persepsi negatif, dan kebersihan mulut, lesi white spot, dan estetika, yang semuanya memberikan persepsi positif yang sama yang dinilai oleh responden. Hal ini cukup baik bagi produsen dan pengguna aligner. Kata kunci Pengguna dan non-pengguna clear aligner, Ibukota negara, persepsi ortodontis.